AI IN MEDICINE: THE FUTURE OF PERSONALIZED HEALTHCARE - Komilova Hilola (Western European Studies, 2024)
Artificial Intelligence (AI) is reshaping the medical landscape by enabling more personalized healthcare. This study explores the applications of AI in diagnostics, treatment, and patient management, highlighting its transformative potential in precision medicine. Methods included a review of current AI applications in healthcare and analysis of their impact. Results demonstrate significant improvements in diagnosis accuracy and treatment efficacy. Challenges such as data privacy and implementation barriers are discussed, with future directions emphasizing ethical AI development and integration into clinical workflows
Keywords: Artificial Intelligence; personalized healthcare; precision medicine